Der "innere Gerichtshof" der Vernunft : Normativitat, Rationalitat und Gewissen in der Philosophie Immanuel Kants und im Deutschen Idealismus - Josifovic, Sasa. (Critical Studies in German Idealism, 2016)
The 11 contributions in Der "innere Gerichtshof" der Vernunft: Normativität, Rationalität und Gewissen in der Philosophie Immanuel Kants und im Deutschen Idealismus explore Immanuel Kant's description of the human conscience as an "internal court of justice". Kant's theory of conscience is discussed in the context of practical philosophy, philosophy of religion and its historical development after Kant, especially in Hegel's philosophy. Approaching general concepts such as \'normativity\' and \'rationality\' from the perspective of Kantian philosophy and German Idealism, the book goes beyond the limited scope of contemporary theories of action that often take these concepts for granted. In particular, Kant's theory of conscience invites different perspectives that are both critical and more fruitful.